(untitled) (Zien Journal of Social Sciences and Humanities, 2022)
This article is dedicated to the main idea of the American cultural space, where the term "modernism" was used in reference to experimental literature and art which, however, did not deny tradition. Opposed to “modernity” appears the term “avant-garde”, which differs from the first by its break with the heritage of past cultural achievements and is accompanied by noisy and radical manifestos. The avant-garde as artistic direction can be seen both as an examination of the classical type of creativity and as an opportunity to update the aesthetic status of modernity. The "poetic renaissance" poetically portray the American reality in all its diversity.